Development and testing of a prototype automatic trim sampler. (July 2017) - Badoni, Madhu; Klassen, Mark D.; Wang, Hui; Youssef, Mohamed K.; Devos, Julia; Gill, Colin O.; Yang, Xianqin
Abstract: The N60 method currently mandated by regulatory bodies in North America for routine testing of beef trim for Escherichia coli O157:H7 requires that 60 slices of beef, up to 375 g, be removed from combo bins containing up to 10, 000 lb of beef trim. The objective of this study was to design and test a prototype automatic trim sampler that would reduce the resource demands of, and result in more representative sampling than, N60. Ten commercial combo bins were each sampled at five locations of each of four levels, by swabbing an area of 1000 cm 2 and by excision of up to five meat pieces with a total area of 100 cm 2 . The samples were enriched in modified Tryptone Soy Broth supplemented with novobiocin at 20 mg/L, and tested for generic E . coli using real-time PCR. A prototype trim sampler was constructed and tested for recovery of aerobes, coliforms and E . coli and was compared to manual swabbing, using beef trim artificially contaminated with E . coli . Overall, 21.5% of excision samples and 38.0% of swab samples from combo bins were positive for E . coli . Of the 40 levels that were sampled, 50.0% were positive by excision, 70.0% were positive by swabbing. The sampler, designed based on swab sampling, could process trim of ≤1 kg. Of the 12 pairs of manual sampling and automatic sampling compared, ≥ 8 were not significantly different for recovering each of the three groups of indicator organisms (P > 0.05). The findings of this study show that swab sampling can be more sensitive and representative than excision sampling for recovering small numbers of E . coli from beef trim and the prototype sampler can have efficacy comparable to manual swabbing for recovering all three groups of indicator organisms from beef. Highlights: 10 combo bins of beef trim were sampled by excision and swabbing at 4 levels per bin. Swab sampling resulted in more samples positive for E. coli than excision sampling. A prototype swabbing-based of an automatic sampler was designed and constructed. The sampler could sample trim of ≤ 1 kg, expected sizes of commercial trim. Bacterial counts from automatic and manual sampling were comparable.